2019
DOI: 10.14295/oh.v25i1.1255
|View full text |Cite
|
Sign up to set email alerts
|

Propagação in vitro de cultivares de alpinia em diferentes fontes de luz

Abstract: The light source in tissue culture is often one of the punctual factors for the adequacy of plant production. For this, light emitting diodes (LEDs) have been used in order to increase the growth and development of the plants propagated in vitro. The objective was to evaluate the in vitro propagation of cultivars of Alpinia purpurata ‘Red Ginger’ and ‘Pink Ginger’ in two different light sources (fluorescent or LEDs tubes). The experiment was conducted in a completely randomized design, factorial scheme (2x2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Seedlings of the Brazilian orchid Cattleya lundii (formerly Microlaelia lundii) showed lower numbers of sprouts when exposed to red and blue LED (Favetta et al, 2017). However, in in vitro propagation of Alpinia cultivars, exposure to white LED for Red Ginger cultivar provided a higher number of sprouts (Pinheiro et al, 2019). This variation in the formation of sprouts between species and cultivars was also reported in the in vitro banana crop, where Rocha et al (2017) evaluated the use of fluorescent lights and LEDs and demonstrated that the use of LED helps sprout development with variations between cultivars.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seedlings of the Brazilian orchid Cattleya lundii (formerly Microlaelia lundii) showed lower numbers of sprouts when exposed to red and blue LED (Favetta et al, 2017). However, in in vitro propagation of Alpinia cultivars, exposure to white LED for Red Ginger cultivar provided a higher number of sprouts (Pinheiro et al, 2019). This variation in the formation of sprouts between species and cultivars was also reported in the in vitro banana crop, where Rocha et al (2017) evaluated the use of fluorescent lights and LEDs and demonstrated that the use of LED helps sprout development with variations between cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…For ornamental plants, information on how the monochromatic light lengths provided by LEDs affect micropropagation are concentrated in the in vitro multiplication and rooting. Different light lengths, many in combination with other factors relevant to tissue culture, have been studied on different ornamental plants (Miler et al, 2019), such as Anthurium (Anthurium andreanum) (Martínez-Estrada et al, 2016), Oncidium tigrinum and Laelia autumnalis (Murillo-Talavera et al, 2016), Microlaelia lundii (Favetta et al, 2017), red ginger (Alpinia purpurata) (Pinheiro et al, 2019), Phalaenopsis amabilisalba Blume (Massaro et al, 2019), Moluccella laevis (Zielińska et al, 2020), Gerbera (Gerbera jamesonii) (Cioć et al, 2021), Pteris aspericaulis var. tricolor (Yu et al, 2021), andBrassavola nodosa (Vendrame et al, 2022).…”
Section: Introductionmentioning
confidence: 99%